2016
DOI: 10.3390/w8120552
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characteristics of Shallow Groundwater in Jiaoshiba Shale Gas Production Area: Implications for Environmental Concerns

Abstract: Abstract:The geochemical characteristics of shallow groundwater are essential for environmental impact studies in the shale gas production area. Jiaoshiba in the Sichuan basin is the first commercial-scale shale gas production area in China. This paper studied the geochemical and isotopic characteristics of the shallow groundwater of the area for future environmental concerns. Results show that the average pH of the shallow groundwater is 7.5 and the total dissolved solids (TDS) vary from 150 mg/L to 350 mg/L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Some studies have assessed the baseline level of the methane content, major ions and typical toxic elements of shallow groundwater in the Fuling shale gas area [16]. However, there is no study on the radioactivity levels of different reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have assessed the baseline level of the methane content, major ions and typical toxic elements of shallow groundwater in the Fuling shale gas area [16]. However, there is no study on the radioactivity levels of different reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (Montcoudiol et al, 2017;Li et al, 2016;Scholes et al, 2016;Eco Logical Australia, 2012;Mair et al, 2012;Susong et al, 2012) have reported that groundwater resource quality monitoring before, during, and after UOG extraction is important to protect groundwater resources. Limited laboratory analytical capacity may, however, hamper effective monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of shale gas resources in China suggest that its gas deposits dwarf those of the US, with 1 115 trillion cubic feet (Tcf) of technically recoverable shale gas resources compared to 665 Tcf in the US (EIA, 2013). China wants to develop these vast deposits (Downie and Drahos, 2017) and places a high premium on the establishment of a groundwater baseline, as well as longterm monitoring to identify groundwater contamination (Li et al, 2016). Li et al (2016) recommend that baseline groundwater monitoring for UOG production be carried out in China for 5 or 6 years before shale gas production.…”
Section: The Global Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, establishing geochemical baseline datasets of shallow groundwater systems before shale gas production is necessary, which can not only provide direct evidence when contamination occurs, but can also reduce controversies of shallow groundwater pollution after hydraulic fracturing [28][29][30]. Currently, a few sites, such as Pennsylvania, USA [31], Colorado, USA [32], Quebec, Canada [33], North Yorkshire, UK [34], and Chongqing, China [35,36], have developed baseline investigation of groundwater before drilling shale gas wells.…”
Section: Introductionmentioning
confidence: 99%